Peningkatan pengetahuan remaja putri tentang manajemen nyeri dismenore melalui terapi kompres air hangat - Utari Ariyanti; Selvia Yolanda Dalimunthe (JOURNAL of Public Health Concerns, 2026)
Background: Dysmenorrhea is a form of menstrual pain frequently experienced by adolescent girls that can interfere with daily activities, academic concentration, and quality of life. Adolescents' limited knowledge regarding dysmenorrhea pain management often leads to inappropriate treatment approaches. Providing education on managing dysmenorrhea pain through warm compresses is crucial, ensuring that adolescents not only understand menstrual pain but are also capable of independently administering appropriate, practical, and safe initial care. Purpose: To improve young women's knowledge of dysmenorrhea pain management through education and a demonstration of warm water compress therapy (a non-pharmacological approach). Method: This community service activity was conducted at Universitas Wirahusada Medan in April 2026. The initiative aimed to provide young women with knowledge regarding dysmenorrhea pain management using warm water compress therapy. Thirty female students participated as respondents. Knowledge levels were assessed using questionnaires administered before (pre-test) and after (post-test) the educational session. A descriptive evaluation based on pre-test and post-test results was conducted to observe the improvement in the students' knowledge. In addition to the knowledge assessment, participants were asked to demonstrate the warm water compress therapy steps to directly evaluate their understanding. Results: The findings showed an increase in respondents' knowledge; prior to the educational activity, the majority of participants (15 individuals or 50.0%) possessed poor knowledge, while only 4 (13.3%) had good knowledge. Following the education, the number of participants with good knowledge rose to 24 (80.0%), and there were no participants with poor knowledge. Additionally, 23 participants (76.7%) were able to perform warm water compress therapy independently, while 7 participants (23.3%) could do so with guidance. Conclusion: Education and demonstration regarding warm water compress therapy are effective in improving the knowledge and skills of adolescent girls in managing dysmenorrhea pain. Suggestion: Similar activities should be conducted on an ongoing basis and reach a wider audience so that adolescent girls can manage menstrual pain independently. Keywords: Adolescent girls; Dysmenorrhea; Non-pharmacological therapy; Warm water compress Pendahuluan: Dismenore merupakan keluhan nyeri haid yang sering dialami remaja putri dan dapat mengganggu aktivitas harian, konsentrasi belajar, serta kualitas hidup. Rendahnya pengetahuan remaja mengenai manajemen nyeri dismenore menyebabkan penanganan yang dilakukan sering kurang tepat. Edukasi mengenai manajemen nyeri dismenore melalui kompres air hangat penting diberikan agar remaja tidak hanya memahami nyeri haid, tetapi juga mampu melakukan penanganan awal yang tepat, praktis, dan aman secara mandiri Tujuan: Untuk meningkatkan pengetahuan remaja putri tentang manajemen nyeri dismenore melalui edukasi dan demonstrasi terapi nonfarmakologis kompres air hangat. Metode: Kegiatan pengabdian masyarakat ini dilaksanakan di Universitas Wirahusada Medan pada bulan April 2026. Sasaran dalam kegiatan ini adalah memberikan pengetahuan tentang manajemen nyeri dismenore dengan terapi nonfarmakologis kompres air hangat pada remaja putri. Kegiatan ini melibatkan sebanyak 30 mahasiswi untuk menjadi responden. Pengukuran nilai pengetahuan responden menggunakan kuesioner yang diberikan sebelum (pretest) dan sesudah kegiatan edukasi (posttest). Evaluasi kegiatan dilakukan secara deskriptif berdasarkan hasil pretest dan posttest untuk melihat peningkatan pengetahuan mahasiswi sebelum dan sesudah mengikuti kegiatan pengabdian masyarakat. Selain evaluasi pengetahuan, peserta juga diminta mempraktikkan kembali langkah-langkah terapi kompres air hangat untuk menilai pemahaman mereka secara langsung. Hasil: Menunjukkan peningkatan pengetahuan responden yaitu sebelum kegiatan edukasi, sebagian besar peserta memiliki pengetahuan kurang sebanyak 15 orang (50.0%) dan pengetahuan baik hanya 4 orang (13.3%). Setelah edukasi, peserta dengan pengetahuan baik meningkat menjadi 24 orang (80.0%) dan tidak ada peserta dengan pengetahuan kurang. Selain itu, 23 peserta (76.7%) mampu melakukan praktik kompres air hangat secara mandiri, sedangkan 7 peserta (23.3%) mampu melakukan dengan arahan. Simpulan: Edukasi dan demonstrasi terapi kompres air hangat efektif meningkatkan pengetahuan dan keterampilan remaja putri dalam manajemen nyeri dismenore. Saran: Kegiatan serupa perlu dilakukan secara berkelanjutan dengan sasaran yang lebih luas agar remaja putri mampu melakukan penanganan nyeri haid secara mandiri.